Narratives of swiss football players about talent - and positive youth development: The role of social agents and agency. - Philipp Koch; Bryan Charbonnet; Noora Ronkainen (Current Issues in Sport Science)
Introduction Recent calls emphasize integrating the literature on positive youth development (PYD) and talent development (e.g. Holt & McDonough, 2024). Both highlight the critical role of proximal social agents within the family (parents, siblings) and the sport subsystem (coaches, peers; Dorsch et al., 2022) while advocating for relational-developmental systems (RDS; Overton, 2015) as a guiding theoretical framework. Central to this framework is the shift from static, one-size-fits-all approaches to a dynamic, idiographic perspective where intertwined relationships between athletes and their social environments influence each other over time. Despite this shift, analyses applying such frameworks in football remain scarce (Verbeek et al., 2023). Through the RDS lens, this study aims to explore the developmental pathways of football athletes by reconstructing how they were shaped by—and actively shaped—their environments from childhood to early adulthood. Specifically, it examines how dynamic interactions with social agents facilitated or hindered their football career and PYD.